How do inpatients' costs, length of stay, and quality of care vary across age groups after a new case-based payment reform in China? An interrupted time series analysis - Ya-jing Chen; Xin-yu Zhang; Xue Tang; Jia-qi Yan; Meng-cen Qian; Xiao-hua Ying (BMC, 2023)
Abstract Context A patient classification-based payment system called diagnosis-intervention packet (DIP) was piloted in a large city in southeast China in 2018. Objective This study evaluates the impact of DIP payment reform on total costs, out-of-pocket (OOP) payments, length of stay (LOS), and quality of care in hospitalised patients of different age. Methods An interrupted time series model was employed to examine the monthly trend changes of outcome variables before and after the DIP reform in adult patients, who were stratified into a younger (18-64 years) and an older group (≥ 65 years), further stratified into young-old (65-79 years) and oldest-old (≥ 80 years) groups. Results The adjusted monthly trend of costs per case significantly increased in the older adults (0.5%, P = 0.002) and oldest-old group (0.6%, P = 0.015). The adjusted monthly trend of average LOS decreased in the younger and young-old groups (monthly slope change: -0.058 days, P = 0.035; -0.025 days, P = 0.024, respectively), and increased in the oldest-old group (monthly slope change: 0.107 days, P = 0.030) significantly. The changes of adjusted monthly trends of in-hospital mortality rate were not significant in all age groups. Conclusion Implementation of the DIP payment reform associated with increase in total costs per case in the older and oldest-old groups, and reduction in LOS in the younger and young-old groups without deteriorating quality of care.